Digital Marketing Skills Search Trends as Human Resource Competency Needs Indicator in Digital Economy Era - Neeltje Martina Walukow (Jurnal Indonesia Sosial Sains, 2026)
The rapid expansion of the digital economy in Indonesia has fundamentally transformed the labor market landscape, particularly in the marketing sector. This research aims to analyze search trends for digital marketing skills using Google Trends data from 2021 to 2026 and correlate these trends with human resource competency needs in the digital era. A quantitative descriptive approach with time series analysis was employed, tracking relative search volumes for eight digital marketing skill keywords: social media marketing, SEO, content marketing, digital marketing strategy, Google Analytics, data analytics marketing, PPC, and email marketing. The findings reveal that social media marketing dominates search trends with an average score of 89.4 out of 100, followed by SEO (76.2) and content marketing (71.8). More significantly, data analytics marketing demonstrated the most substantial cumulative growth of 171.1% over the five-year period. Correlation analysis using Pearson and Spearman methods confirmed a strong positive relationship between search volume and actual job market demand (r = 0.894, p < 0.001). Monthly job posting data were collected from Jobstreet Indonesia and LinkedIn Economic Graph reports through secondary dataset aggregation between 2021–2026. The data were standardized into comparable monthly indices before cross-correlation analysis, establishing Google Trends as a valid leading indicator for workforce competency forecasting. These findings indicate that Indonesia's labor market is undergoing a fundamental shift from traditional marketing competencies toward integrated, data-driven digital skills. The study provides practical implications for curriculum developers, HR practitioners, and policymakers in formulating responsive workforce development strategies.